Sejarah Kampung Qurani: Artikulasi Islam Lokal di Bandar Setia, Deli Serdang, Sumatera Utara - Hendra Kurniawan; Suryo Adi Sahfutra (UIN Sumatera Utara Medan, 2017)
This research begins with the emergence of the name 'Kampung Qur'ani' in the village of Bandar Setia. As a heterogeneous village of ethnic and religious aspect, Bandar Setia located in the outskirts of Medan became iconik how the implementation of the 'pilot project' the idea of kampung Qur'ani. This study focuses on the historical aspect of why Kampung Qur'ani can emerge with the socio-historical setting that accompanies it. It also discusses how the idea is run, with all the challenges and conveniences that exist. The result of this research are: 1) The emergence of Kampur Qur'ani is an effort to build a new stigma that has been negatively attached to the Village of Setia, a positive image whose hope can give a new nuance to the surrounding community; 2) Kampur Qur'ani emerged because of anxiety of religious leaders in the area of Bandar Setia because of the situation of people who are far from Islamic values; 3) the strategy of forming the value of qur'ani is done through various movements, namely free nursing school for children, dawn movement in congregation and various activities of syiar qur'an that have been held; 4) The challenge of implementing Kampung Qur'ani ideas among others is, there are still many uneducated societies in mass organizing, institutional and financial management as well as community involvement that has not been fully active in the movement.